Inflammatory perturbations in early life long-lastingly shape the transcriptome and TCR repertoire of the first wave of regulatory T cells - Yang, Juhao; Zou, Mangge; Chu, Xiaojing; Floess, Stefan; Li, Yang; Delacher, Michael; Huehn, Jochen (Frontiers in Immunology, 2022)
The first wave of Foxp3+ regulatory T cells (Tregs) generated in neonates is critical for the life-long prevention of autoimmunity. Although it is widely accepted that neonates are highly susceptible to infections, the impact of neonatal infections on this first wave of Tregs is completely unknown. Here, we challenged newborn Treg fate-mapping mice (Foxp3eGFPCreERT2xROSA26STOP-eYFP) with the Toll-like receptor (TLR) agonists LPS and poly I:C to mimic inflammatory perturbations upon neonatal bacterial or viral infections, respectively, and subsequently administrated tamoxifen during the first 8 days of life to selectively label the first wave of Tregs. Neonatally-tagged Tregs preferentially accumulated in non-lymphoid tissues (NLTs) when compared to secondary lymphoid organs (SLOs) irrespective of the treatment. One week post challenge, no differences in the frequency and phenotypes of neonatally-tagged Tregs were observed between challenged mice and untreated controls. However, upon aging, a decreased frequency of neonatally-tagged Tregs in both NLTs and SLOs was detected in challenged mice when compared to untreated controls. This decrease became significant 12 weeks post challenge, with no signs of altered Foxp3 stability. Remarkably, this late decrease in the frequency of neonatally-tagged Tregs only occurred when newborns were challenged, as treating 8-days-old mice with TLR agonists did not result in long-lasting alterations of the first wave of Tregs. Combined single-cell T cell receptor (TCR)-seq and RNA-seq revealed that neonatal inflammatory perturbations drastically diminished TCR diversity and long-lastingly altered the transcriptome of neonatally-tagged Tregs, exemplified by lower expression of Tigit, Foxp3, and Il2ra. Together, our data demonstrate that a single, transient encounter with a pathogen in early life can have long-lasting consequences for the first wave of Tregs, which might affect immunological tolerance, prevention of autoimmunity, and other non-canonical functions of tissue-resident Tregs in adulthood.